Ewch ati! 1940 (1940)
1940 1939-1945 "Ewch ati! 1940" [HFR0227], 1940 This Welsh language leaflet was distributed to war workers in Wales. A translation reads'Workers - your job is as vital as that of the Soldier, Sailor or Airman. The Nation demands the greatest and fastest output ever asked for in history. Do not let the Forces down. They serve day and night. Every moment you work give of your very best. Listen to no rumour. Despise the slacker. Every job is vital. Every moment wasted is a gift to the enemy. Put your back into your job. Remember Mr Herbert Morrison's words " GO TO IT!" '